Impact of 10-undecenal PVA acetalization on the macromolecular organization and the viscosity of aqueous solutions. Surface and bulk properties of the modified PVA films. (November 2018) - Piluso, P.; Sudre, G.; Boisson-Da Cruz, F.; Bounor-Legaré, V.; Espuche, E.
Graphical abstract: Highlights: PVA acetalization was carried out in aqueous medium for low acetalization degrees. PVA chain organization in aqueous solution was investigated through SAXS analysis. Newtonian viscosity of acetalized PVA solutions was investigated. The grafted segments amount located at film surface was quantified. Abstract: PVA acetalization by 10-undecenal was carried out in aqueous medium in order to obtain PVA with acetalization degree (AD) ranging from 0.36 up to 1.85 mol%. PVA chain organization in 8 wt% aqueous solutions was investigated through Small Angle X-ray Scattering measurements. The significant modification of macromolecules organization evidenced at the AD value of 0.6 mol% was explained by reinforced polymer-polymer interactions as a consequence of hydrophobic grafts on the polymer chains. Newtonian viscosity of acetalized PVA solutions was also significantly increased for AD above 0.6 mol%. A chemical labeling method was developed to prove the presence of grafted segments at the surface of the films prepared from modified PVAs. The concentration of grafted moieties at the surface increased significantly above 0.8–0.9 mol% AD and attained a value of 27 µmol m −2 for an AD value of 1.48 mol%.